Identification of risk factors for an unsuccessful transition from pediatric to adult sickle cell disease care. Issue 4 (18th December 2013) - Andemariam, Biree; Owarish‐Gross, Jasmine; Grady, James; Boruchov, Donna; Thrall, Roger S.; Hagstrom, J. Nathan
<x xml:space="preserve">Abstract</x> Background A successful transition from pediatric to adult sickle cell disease (SCD) care is paramount to continued improvements in survival. In order to enhance transition success, our pediatric SCD transition process was modified to include combined adult and pediatric provider clinics that incorporated participation by our local SCD community‐based organization. All children ages 16 and over participated in this newly‐formed transition program. Procedure After 5 years of implementation of the modified SCD transition program, we retrospectively studied clinical and non‐clinical risk factors for an unsuccessful transition. Risk factor categories studied included patient demographics, transition clinic attendance, and disease severity. Results Thirty‐two percent of patients did not transition successfully. Demographic factors such as gender, race, and type of insurance did not influence transition outcome, although travel distance to the adult SCD center was an identifiable risk factor for an unsuccessful transition. While transition clinic attendance rate did not affect transition outcomes, older age at first modified combined transition clinic visit was a significant risk factor for lack of transition. Patients with clinical markers of milder disease severity (SC and Sβ+ genotypes and no chronic transfusion therapy) were at higher risk for an unsuccessful transition than patients with severe disease. Conclusions We have identified several risk factors for lack of transition success which will allow us to modify our transition efforts going forward to capture this highest risk subset. Pediatr Blood Cancer 2014;61:697–701. © 2013 Wiley Periodicals, Inc.